BRIEF REPORT ON THE TERRITORIAL OCCUPATION PROCESS OF BRAZIL: AMAZON CASE STUDY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Brazil occurred through a colonization process based on the possession and use of land, which began in 1500. Throughout the history of this country, which culminated in the Federative Republic of Brazil, land continued to be the center of the economy, and an increasingly immovable asset. more valued. The regulation of Public Law considers this asset as an item of value that must be protected in the best possible way, and this same relationship is reflected in today's society, in which economic-social policy aims to accumulate assets and protect assets already acquired. . The legal provisions end up maintaining the concentration of land, therefore the concentration of capital for a small portion of the population, in a modus operandi similar to what occurred at the time of Colonial Brazil, thus being a continuous, recurring and living cycle. In this way, it would not be unusual for Brazil, a country driven economically by primary-based means, that is, agroextractive production, from its beginnings to the present day, to protect the holders of these means of production in all aspects. In this context, this study analyzes land distribution as a method of obtaining and concentrating power, but engendered as a justification for social well-being. But in fact, it is justified only by the desire for a certain social segment to be successful, which ends up bringing social imbalance and negative consequences in the lives of a large part of the Brazilian population.